2012
DOI: 10.5194/acpd-12-9903-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deliquescence, efflorescence, and phase miscibility of mixed particles of ammonium sulfate and isoprene-derived secondary organic material

Abstract: The hygroscopic phase transitions of ammonium sulfate mixed with isoprene-derived secondary organic material were investigated in aerosol experiments. The organic material was produced by isoprene photo-oxidation at 40% relative humidity. The low volatility fraction of the photo-oxidation products condensed onto ammonium sulfate particles. The particle-phase organic material had oxygen-to-carbon ratios of 0.67 to 0.74 for mass concentrations of 20 to 30 μg m<sup>&minus;3</sup>. The deliquescenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 54 publications
7
39
0
Order By: Relevance
“…Hygroscopic experiments demonstrated that haze particles collected in the YRD deliquesced at 68-70%, at lower RH than ammonium sulfate and continuously grew with increasing RH (Figure 8b), in agreement with the deliquesced properties of aerosol particles at a suburban site in the NCP [Liu et al, 2011]. Numerous laboratory studies have shown that organic coatings on inorganic particles induce a lower DRH compared to that of the pure inorganic compounds [Peckhaus et al, 2012;Pope et al, 2010;Smith et al, 2012;Wu et al, 2011]. Also, the mixed-salt aerosols generally deliquesce earlier than the single-salt aerosols, and internally mixed hydrophobic inorganic particles do not change the DRH of salts within the individual particles [Freney et al, 2009;Tang, 1997;Wise et al, 2007].…”
Section: Hygroscopicity Of Particlessupporting
confidence: 75%
“…Hygroscopic experiments demonstrated that haze particles collected in the YRD deliquesced at 68-70%, at lower RH than ammonium sulfate and continuously grew with increasing RH (Figure 8b), in agreement with the deliquesced properties of aerosol particles at a suburban site in the NCP [Liu et al, 2011]. Numerous laboratory studies have shown that organic coatings on inorganic particles induce a lower DRH compared to that of the pure inorganic compounds [Peckhaus et al, 2012;Pope et al, 2010;Smith et al, 2012;Wu et al, 2011]. Also, the mixed-salt aerosols generally deliquesce earlier than the single-salt aerosols, and internally mixed hydrophobic inorganic particles do not change the DRH of salts within the individual particles [Freney et al, 2009;Tang, 1997;Wise et al, 2007].…”
Section: Hygroscopicity Of Particlessupporting
confidence: 75%
“…In fact, at RH > 60% isoprene SOA has a viscosity of a liquid, therefore creating the conditions for reactions in the condensed phase (wet aerosol) to occur. 62 , 84 This is supported by aqueous-phase experiments performed for a longer reaction time, where we have observed a wider variety of different and longer oligomers compared to experiments performed with a shorter reaction time ( Figure S3 ). In general, on the one hand, SOA produced at high RH is characterized by many different and longer oligomers compared to experiments started in dry conditions in contrast to what was observed in previous experiments by Nguyen et al 15 On the other hand, Rodigast et al 46 observed a dependence of oligomer formation from methylglyoxal not only on RH but also on pH of seed particles, which may partly explain our results, as methylglyoxal is one of the reaction products.…”
Section: Resultssupporting
confidence: 67%
“…At this RH, the predicted T g for 1 : 1 C6/C10 is 185 K. Using Eq. (1), η for 1 : 1 C6/C10 is approximately 6.4 × 10 5 Pa s. Similarly, at 210 K, ice nucleated on C6/C10 and C6/C10/AS at 74.0 % RH, which correlates to a predicted T g of 181 K and an η of approximately 3.7 × 10 5 Pa s. Thus, at 210 and 215 K, pure C6/C10 and the C6/C10 coatings are considered amorphous semi-solids (Shiraiwa et al, 2011). Zobrist et al (2011) have shown that the diffusion coefficients for a small molecule like water diffusing through a glassy matrix at room temperature is ∼10 −10 cm 2 s −1 ; however, the diffusion constant was observed to decrease strongly with decreasing temperature.…”
Section: Ice Nucleation On Solid Amorphous Organic Particles Above Thmentioning
confidence: 89%
“…To the authors' knowledge, no such measurements have been made at temperatures relevant to this study. Shiraiwa et al (2011) have measured the diffusion of the small molecule ozone through an amorphous semi-solid matrix at room temperature to be ∼10 −7 to 10 −9 cm 2 s −1 . If a similar, strong temperature dependence followed for amorphous semi-solids, the time for a water molecule to diffuse through a 1 µm semi-solid shell may take much longer than that timescales of our ice nucleation experiments.…”
Section: Ice Nucleation On Solid Amorphous Organic Particles Above Thmentioning
confidence: 99%